India in South Asia: Interaction with Liberal Peacebuilding Projects. (June 2018) - Adhikari, Monalisa
In fragile and conflict-affected States 1 (henceforth FCAS) in South Asia, two distinct forms of international engagement have worked simultaneously—the engagement of India, the regional hegemon, and that of Western states that promote liberal peacebuilding projects. From Norwegian engagement in Sri Lanka to European Union (EU) and United Nations (UN) engagement in Myanmar, to the UN-led international engagement in Nepal, liberal peacebuilding, despite its fault lines, has ubiquitous presence in South Asia, a region fraught with different forms of conflict and fragility. The norms, practices and modalities of engagement of India as well as of liberal peacebuilding projects have their distinct specificities in their normative foundations, practices and modalities of engagement. This article contends that the current interaction, though often unacknowledged, is marked by uncertainties, contrasts, instrumental use of norms, lack of coordination and even unexpected overlaps. This article primarily argues that in order for India to play a constructive role in the region, it needs to devise a policy on how it engages with liberal peacebuilding norms and its diffusion in practice through a variety of organisational and institutional networks.